Islamic studies analysis of Abai's beliefs in poems written between 1855-1891 (Eurasian Journal of Religious Studies, 2024)
Abai is the main Kazakh poet, thinker, great sage, one of the main figures of his time. Specialists from all fields of science became intrigued by Abai's works and proceeded to analyze them through the lens of their respective disciplines. In this article, we will focus on religious faiths - aqida of Abai. Islamic studies is a consisting of several large areas, and the most important of them is the field kalam. The sphere that defines a person's religiousness and religious faith is aqida. In this article, the object of study will be the religious worldview of Abai. An Islamic, religious, and theolinguistic analysis of Abai's works will be conducted, from his first poems to the period of his younger Ospan's death. The topics concerning the Islamic faith that Abai raised in his poems during a given period will be determined and on the basis of these topics an analysis of the beliefs of the great thinker will be carried out. An attempt will also be made to show the roots of Abai's beliefs coming from the sacred texts of Islam - Koran and Sunnah. Keywords: Allah, the Only God, transient world, fate, Ayat, Hadith